2020
DOI: 10.1002/jbt.22463
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐3 mediates pulmonary vascular endothelial cell dynamics via TRPC1/4 under acute hypoxia

Abstract: Galectin-3 (Gal-3) has been implicated in various biological functions, yet little is known about its role in regulating the dynamics of pulmonary vascular endothelial cells. Gal-3 was shown to be increased in hypoxic model rats by sequencing analysis. We exposed pulmonary vessel endothelial cells (PVECs) to hypoxia or Gal-3 stimulation, following which cell apoptosis and autophagy were measured with the relevant methods. The results demonstrated that hypoxia elevated nuclear factor-κB (NF-κB) activity and Gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Our results showed that hypoxia induced Akt inactivation, but treatment with Akt agonists or blockers reversed the change in Sec23 after Ndrg1 interference, indicating that Ndrg1 regulates Sec23 through Akt pathways. Moreover, Akt pathways were reported to play a role in PAH (de Jesus Perez et al, 2014;Li et al, 2020), and our results also showed that the pathways were involved in PASMC proliferation after hypoxia. Furthermore, we observed that Ndrg1 was enhanced and mainly expressed in the cytoplasm, while Sec23 was weakened, mainly in the nucleus after hypoxia stimulation through immunofluorescence, indicating that there were differences in expression in time and space between the two proteins.…”
Section: The Therapeutic Effect Of Tex261 On Rats With Pulmonary Arte...supporting
confidence: 79%
“…Our results showed that hypoxia induced Akt inactivation, but treatment with Akt agonists or blockers reversed the change in Sec23 after Ndrg1 interference, indicating that Ndrg1 regulates Sec23 through Akt pathways. Moreover, Akt pathways were reported to play a role in PAH (de Jesus Perez et al, 2014;Li et al, 2020), and our results also showed that the pathways were involved in PASMC proliferation after hypoxia. Furthermore, we observed that Ndrg1 was enhanced and mainly expressed in the cytoplasm, while Sec23 was weakened, mainly in the nucleus after hypoxia stimulation through immunofluorescence, indicating that there were differences in expression in time and space between the two proteins.…”
Section: The Therapeutic Effect Of Tex261 On Rats With Pulmonary Arte...supporting
confidence: 79%
“…Features including stress to endothelial cells and their corresponding apoptosis are noticed in PAH individuals (4). As known studies and our pilot observation have shown, pulmonary vascular endothelial cell (PVEC) injury is one of the pathogeneses of PAH (e.g., decreased Notch1 in PVECs) (5)(6)(7).…”
Section: Introductionmentioning
confidence: 72%
“…Studies have shown that Gal-3 activates the Wnt/βcatenin signalling pathway and then regulates cell proliferation, invasion, and migration [43,44]. The interaction of Gal-3 and B-cell lymphoma-2 (Bcl-2) generates cell apoptotic events and restrains autophagy via the (TRPC1/4) signalling pathway and Akt phosphorylation of glycogen synthase kinase-3β (GSK-3β) [45,46]. Gal-3 also modulates cell apoptosis by interacting with synexin [47], nucling [48] and CD95 (APO-1/Fas) [49].…”
Section: The Biological Functions Of Gal-3mentioning
confidence: 99%